The Role of Sports Management in Promoting the Participation of Individuals with Disabilities in School Sports Activities - Hammad, Saleh; Abumariam , Anan (Journal of Ecohumanism, 2025)
This study seeks to examine the function of sports administrations in facilitating the involvement of individuals with disabilities in school sports activities, emphasizing the aspects that affect the establishment of a complete and suitable environment for this demographic. Data were gathered via a questionnaire administered to 82 principals of schools for individuals with disabilities, focusing on the sports programs offered, required adaptations to accommodate the needs of individuals with disabilities, students’ reactions to these activities, and variables influencing their participation, including gender, age group, and type of disability. The findings indicated that sports administrators foster a conducive atmosphere, as students with disabilities exhibited a favorable inclination to engage in sports activities, with variations in participation levels noted according to disability type and age group. Research indicates that sports policies and procedures implemented in schools enhance the involvement of individuals with disabilities; yet, certain areas require enhancement, particularly in providing further adjustments to accommodate students’ requirements. The statistical study revealed a favorable and statistically significant correlation between the function of sports administrations and the enhancement of participation among individuals with disabilities in sports activities. This research elucidates the significant role of sports administrations in facilitating equitable opportunities for individuals with disabilities within the sports domain, and offers recommendations to enhance these opportunities and foster the inclusive participation of this demographic in school sports activities.